2021
DOI: 10.25259/sni_507_2021
|View full text |Cite
|
Sign up to set email alerts
|

Parasagittal cystic meningioma mimicking hemangioblastoma: A case report

Abstract: Background: Cystic meningioma is a rare variety with similar histological profiles like the solid tumors. It has been documented in both supratentorial and infratentorial compartments presenting radiologically as a large cyst with mural nodule mimicking hemangioblastoma. Case Description: We managed a middle-aged woman who presented with recurrent seizures and brain MRI revealed left frontal cystic parasagittal tumor with mural nodule. She had left frontal awake craniotomy and gross total tumor excision. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…[41][42][43][44][45][46][47] All studies, except 4, reported AC on tumors only (78.9%). 22,23,26,29,31,32,[34][35][36][37][38][39][40] 1 study (5.3%) reported AC in epilepsy, 25 whereas 3 studies (15.8%) reported other surgical indications in addition to tumor 24,30,33 (Supplementary Table 3, http://links.lww.com/NEU/D712).…”
Section: Overview Of Literature Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[41][42][43][44][45][46][47] All studies, except 4, reported AC on tumors only (78.9%). 22,23,26,29,31,32,[34][35][36][37][38][39][40] 1 study (5.3%) reported AC in epilepsy, 25 whereas 3 studies (15.8%) reported other surgical indications in addition to tumor 24,30,33 (Supplementary Table 3, http://links.lww.com/NEU/D712).…”
Section: Overview Of Literature Search Resultsmentioning
confidence: 99%
“…Sixteen studies (84.2%) provided information on operation time. [22][23][24][25][26][27][28][30][31][32][34][35][36][37]39,40 The longest mean operation time was more than 237 minutes, 24 whereas the shortest operation time was 1 hour 33 (Supplementary Table 3, http://links.lww.com/NEU/D712).…”
Section: Overview Of Literature Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations